UNDERSTANDING DISORGANIZED SCHIZOPHRENIA THROUGH THE NARRATOR’S DESCRIPTION OF HIS MENTAL ILLNESS IN EDGAR ALLAN POE’S THE TELL TALE HEART - Suci Suryani (Prosodi Jurnal Ilmu Bahasa dan Sastra, 2014)
The male main character presented as the narrator in Poe’s The Tell Tale Heart is the interesting one described by Edgar Allan Poe. He is described as the character who suffers from the mental illness. He feels really anxious as he sees the old man’s eyes so that the feeling drives him to murder and mutilate the old man. How are the symptoms and type of mental illnes experienced by the narrator described by the short story? and how do the psychological problems give impacts to his life? are the two questions formulated in the study to understand the mental illness from which the male main character suffers. Here, literature can be discussed based on the psychological perspective. Hence, it needs literature and psychology and psychological criticism. Furthermore, to discuss further about what happens with the narrator’s psychology, it needs the psychological theory focusing to schizophrenia. Qualitative research is established to analyze the narrator’s utterances as the data. It is described that the narrator experiences anxious, delusion, and auditory hallucination. The two symptoms prove that he suffers from disorganized schizophrenia. This syndrome is marked by the narrator who experiences disorganized speech and behaviour. This syndrome makes the narrator desires to kill, kills, mutilates, deposits the old man without knowing the reason, and admits the deed.